The relative importance of volunteer tourism (sustainable/pro-social form of tourism) motivation factors for young tourists: a descriptive analysis by continents, gender, and frequency - Han, Heesup; Lee, Soyeun; Meng, Bo; Chua, Bee Lia; Ryu, Bobby Hyungseo (MDPI, 2020)
Volunteer tourism is a vital formation of altruistic and sustainable tourism. This research is aimed to empirically find the relative importance of the motivation factors and the motivation realization factors for young tourists participating in the global volunteer tourism programs. The differences in the study variables across continents, gender, and frequency of participation were also scrutinized. A quantitative research approach that utilized the survey method was employed. The outcomes showed that personal development was the most vital motivator for global volunteer tourism. On the other hand, the young tourists felt that they most realized the factor of a new experience through their recent international volunteer tourism experience. The motivation factors and the motivation realization factors were consistent across the continents. Furthermore, the mean differences in the motivations, the motivations’ realization, satisfaction, and the behavioral intentions were revealed to be non-significant for the genders and the frequency of volunteer participation. By grasping the young volunteer tourists’ motivations and the experience evaluations, the volunteer programs can be advanced in consonance with their necessities and demands, which enhance the volunteer tourism experience.